Stress, self-care, and wellbeing: a study on the experiences of educational leaders in NEMSU - Nemesio G. Loayon; Erwin B. Berry; El Dixon G. Plazo (Institute of Advanced Engineering and Science, 2026)
The wellbeing of educational leaders is a critical concern, particularly in resource-constrained higher education institutions. This study aimed to explore the experiences of educational leaders at North Eastern Mindanao State University (NEMSU) by identifying their primary sources of stress, examining the perceived impacts on wellbeing and job performance, and assessing their self-care practices, as well as determining the relationships among these variables. Using a descriptive correlational design, data were collected from 117 educational leaders through a validated survey instrument with a reliability coefficient of 0.828. Descriptive statistics and Spearman rank-order correlation were used to analyze relationships among stress sources, impacts, and self-care. Results showed that administrative tasks, role overload, and limited institutional resources are the main stressors, significantly affecting health, cognitive functioning, job performance, and family life. Self-care practices such as social support, spiritual routines, and work boundaries were moderately practiced but showed no significant relationship with stress reduction or its impacts. These findings emphasize the limits of individual coping strategies and the need for institutional support. The study suggests refining the job demands-resources (JD-R) model and conservation of resources (COR) theory to account for organizational and cultural factors in developing country contexts, with implications for leadership development, stress management, and institutional policy reforms.